Nano-scale liposomal container with a «signal system» for substances delivering in living cells - Yefimova, S.L.; Lebed, A.S.; Guralchuk, G.Ya.; Sorokin, A.V.; Kurilchenko, I.Yu.; Kavok, N.S.; Malyukin, Yu.V. (Вiopolymers and Cell, 2011)
Aim. The aim of this research is to study the possibility to supply the nano-scale liposomal «container», used for the targeted substance delivery inside the living cells, with a «signal system» to trace the liposome fate in real time. Methods. For this purpose, the methods of fluorescence microscopy, fluorescence spectroscopy and microspectroscopy have been used. Results. The cellular uptake of hydrophobic fluorescent probes DiO and DiI, preloaded in phosphatidylcholine (PC) liposomes, in real time has been studied using fluorescence resonance energy transfer (FRET) from the donor probe DiO to the acceptor one DiI. It has been revealed that after 3 hours incubation of hepatocytes with FRET liposomes, the FRET signal almost disappears, whereas DiO fluorescence becomes very intensive. Conclusions. The loss of FRET signal could be used as a «signal system» to monitor the cell-liposome fusion and delivery of any active compounds to cells. Key words: liposomes, fluorescent probes, cells, fluorescence resonance energy transfer.